Supported catalyst, preparation method thereof and fuel cell

By loading nanometal particles on the shallow pore section of the modified porous carbon support in the fuel cell, the problem of catalyst poisoning is solved, the mass transfer distance is shortened, and the power generation efficiency of the fuel cell is improved.

CN119725586APending Publication Date: 2025-03-28SUZHOU HYDROGINE POWER TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411916019.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The supported catalysts in the existing fuel cells are susceptible to toxicity by sulfonic acid groups in the ionomer, resulting in a decrease in the activity of the catalyst and the inability to effectively promote the reaction between hydrogen and oxygen, thereby reducing the power generation efficiency of the fuel cells.

Method used

By mixing the modified porous carbon support with the precursor solution, the nanometal particles are modified in a direction direction so that they are loaded on the shallow pore section of the pore, isolating the direct contact between the nanometal particles and the ionomer, protecting the nanometal particles from being poisoned, and at the same time shortening the mass transfer distance and maintaining the porous properties of the supported catalyst.

Benefits of technology

Effectively protect nanometal particles from being toxic to sulfonic acid groups in the ionomer, shorten the mass transfer distance, improve the power generation efficiency of the catalyst, and ensure the porous performance of the supported catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725586A_ABST
    Figure CN119725586A_ABST
Patent Text Reader

Abstract

The invention discloses a supported catalyst, a preparation method thereof and a fuel cell, and belongs to fuel cells. The preparation method of the supported catalyst comprises the following steps: mixing a modified porous carbon carrier and a precursor solution to obtain an intermediate product; the modified porous carbon carrier is provided with a hole, the hole is provided with an opening penetrating through the surface of the modified porous carbon carrier, the hole is provided with a shallow hole section close to the opening and a deep hole section deviating from the opening, the wall surface, located on the shallow hole section, of the hole is modified with a hydrophilic group, and the precursor solution contains metal ions used for being coordinated with the hydrophilic group; the metal ions comprise at least one of noble metal ions and transition metal ions. And the intermediate product is subjected to reduction treatment, so that the metal ions are reduced into nano metal particles. According to the preparation method, the nano metal particles can be directionally modified at specific parts in holes of the porous carbon carrier, and the nano metal particles are loaded in shallow hole sections of the holes, so that the nano metal particles can be protected from being poisoned by sulfonic acid groups in an ionomer, and the mass transfer distance can be shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cells, and in particular, to a supported catalyst and a preparation method thereof, and a fuel cell. Background Art

[0002] Currently, supported catalysts widely used in electrochemical energy devices such as fuel cells suffer from catalyst poisoning during actual application. The poisoned catalyst cannot effectively promote the reaction of hydrogen and oxygen, resulting in a decrease in the power generation efficiency of the fuel cell. The use of porous carbon carriers can increase the specific surface area of ​​the carrier by utilizing its complex and fine pore structure, improve the dispersion of nano-metal particles, such as platinum and other precious nano-metal particles, and at the same time, loading them in the pores can avoid direct contact between metal particles and ionomers, reducing the poisoning effect. However, the metal particles located in the deep holes need a longer mass transfer path to participate in the catalytic reaction, which reduces the catalytic efficiency. Summary of the invention

[0003] The present application provides a supported catalyst, a preparation method thereof and a fuel cell. The preparation method is convenient for scaled-up production, and the prepared supported catalyst can protect nano-metal particles from being poisoned by sulfonic acid groups in the ionomer, and is beneficial for shortening the mass transfer distance, while ensuring the porous properties of the supported catalyst, so that the power generation efficiency of the fuel cell can be improved after its application in the fuel cell.

[0004] The embodiment of the present application is implemented as follows:

[0005] In a first aspect, the present application provides a method for preparing a supported catalyst, which comprises the following steps:

[0006] mixing the modified porous carbon support and the precursor solution to obtain an intermediate product;

[0007] The modified porous carbon carrier has holes, the holes have openings that penetrate the surface of the modified porous carbon carrier, the holes have shallow hole sections close to the openings and deep hole sections away from the openings, the walls of the shallow hole sections are modified with hydrophilic groups, the precursor solution contains metal ions for coordinating with the hydrophilic groups, and the metal ions include at least one of noble metal ions and transition metal ions.

[0008] The intermediate product is subjected to reduction treatment to reduce the metal ions to nano-metal particles.

[0009] The preparation method provided in the present application can realize the directional modification of nano-metal particles at specific locations in the pores of the porous carbon carrier, so as to realize the regulation of the loading position of the metal catalyst, and load the nano-metal particles in the shallow hole section of the hole (that is, the superficial position). This loading site can not only isolate the direct contact between the nano-metal particles and the ionomer, protect the nano-metal particles from being poisoned by the sulfonic acid groups in the ionomer, but also help to shorten the mass transfer distance, while avoiding the deposition of nano-metal particles in the deep hole section to block the pores and increase the mass transfer resistance, thereby ensuring the porous performance of the supported catalyst.

[0010] In some optional embodiments, the hydrophilic group includes at least one of an oxygen-containing group and a nitrogen-containing group;

[0011] Wherein, the nitrogen-containing group includes at least one of amino, nitro, pyrrole N, pyridinic N, and graphite N;

[0012] The oxygen-containing group includes at least one of a carboxyl group, a carbonyl group, and a hydroxyl group;

[0013] Optionally, the precious metal ions include at least one of platinum ions, palladium ions, rhodium ions, gold ions, and silver ions, and the transition metal ions include at least one of manganese ions, chromium ions, iron ions, cobalt ions, nickel ions, copper ions, and zinc ions.

[0014] In some optional embodiments, the method for preparing the modified porous carbon support comprises:

[0015] mixing the porous carbon support with a solvent so that the porous carbon support is in a saturated state to obtain a first support;

[0016] Drying once to make the first carrier lose part of the solvent, so that the part of the pores not filled with the solvent is used as a shallow pore section, and the part of the pores filled with the solvent is used as a deep pore section, thereby obtaining a second carrier;

[0017] Performing hydrophilic treatment on the second carrier to form hydrophilic groups on the shallow hole section of the hole and the surface of the second carrier to obtain a third carrier;

[0018] The third carrier is mixed with a solvent to make the third carrier in a saturated state, the hydrophilic groups on the surface of the third carrier are removed, and secondary drying is performed to obtain a modified porous carbon carrier.

[0019] In some optional embodiments, the liquid loss rate of the second carrier is 10%-30% compared to the first carrier.

[0020] In some optional embodiments, the primary drying temperature is 40°C-80°C.

[0021] In some optional embodiments, the hydrophilic treatment method includes plasma hydrophilic modification treatment, the atmosphere of the plasma hydrophilic modification treatment includes at least one of oxygen, nitrogen, and ammonia, the temperature of the plasma hydrophilic modification treatment is 25°C-40°C, the time of the plasma hydrophilic modification treatment is 10min-60min, and the power of the plasma hydrophilic modification treatment is 50W-300W.

[0022] In some optional embodiments, the step of removing the hydrophilic groups located on the surface of the third carrier includes: performing hydrogen plasma treatment on the surface of the third carrier in a saturated state, the time of the hydrogen plasma treatment is 10min-60min, the temperature of the hydrogen plasma treatment is 25℃-40℃, and the power of the hydrogen plasma treatment is 50-300W.

[0023] In some optional embodiments, the solvent is at least one of water and C1-C4 alcohol.

[0024] In some optional embodiments, the restoration process includes:

[0025] In the liquid phase, the metal ions are reduced to nano-metal particles by the action of a reducing agent; or,

[0026] The intermediate product is heat treated in a reducing atmosphere to reduce the metal ions to nano-metal particles.

[0027] In a second aspect, the present application provides an example of a supported catalyst, which is prepared by the preparation method provided in the first aspect of the present application;

[0028] The supported catalyst includes modified porous carbon and nano-metal particles, and the nano-metal particles are located on the wall surface of the pores located in the shallow hole section.

[0029] The supported catalyst provided by the present application, wherein the nano-metal particles are supported in the shallow hole section of the hole (i.e., the superficial position), the supported site can not only isolate the direct contact between the nano-metal particles and the ionomer, protect the nano-metal particles from being poisoned by the sulfonic acid groups in the ionomer, but also help to shorten the mass transfer distance, and at the same time avoid the deposition of nano-metal particles in the deep hole section so that the pores are blocked and the mass transfer resistance is increased, thus ensuring the porous performance of the supported catalyst. In summary, the supported catalyst can improve the power generation efficiency of the fuel cell after being applied to the fuel cell.

[0030] In a third aspect, the present application provides an example of a fuel cell, which includes the supported catalyst provided in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 A schematic diagram of the structure of the supported catalyst provided in this application;

[0033] Figure 2 This is a schematic diagram of the preparation process of the supported catalyst provided in Example 1 of the present application.

[0034] Icons: 100-supported catalyst; 11-modified porous carbon; 12-pores; 20-nanometallic particles. DETAILED DESCRIPTION

[0035] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0036] The main reason why the utilization rate of nanometal particles is not favorable in the supported catalysts widely used in electrochemical energy devices such as fuel cells is that under actual working conditions, the precious metal nanoparticles in these microporous structures cannot contact the electrolyte due to excessive deposition, or the pores are blocked due to excessive deposition, thereby increasing the mass transfer resistance, causing a significant reduction in the utilization rate of the nanometal particles. In addition, the directly exposed precious metal nanoparticles are in direct contact with the sulfonic acid groups of the ionomer, resulting in catalyst poisoning, reducing its activity and making it unable to effectively promote chemical reactions.

[0037] In view of this, this application is hereby filed.

[0038] The following is a detailed description of the supported catalyst, preparation method thereof and fuel cell according to the embodiments of the present application:

[0039] The first aspect of the present application provides a method for preparing a supported catalyst, which comprises the following steps:

[0040] mixing the modified porous carbon support and the precursor solution to obtain an intermediate product;

[0041] The modified porous carbon carrier has holes, the holes have openings that penetrate the surface of the modified porous carbon carrier, the holes have shallow hole sections close to the openings and deep hole sections away from the openings, the walls of the shallow hole sections are modified with hydrophilic groups, the precursor solution contains metal ions for coordinating with the hydrophilic groups, and the metal ions include at least one of noble metal ions and transition metal ions.

[0042] The intermediate product is subjected to reduction treatment to reduce the metal ions to nano-metal particles.

[0043] Among them, it can be understood that the shallow hole segment and the deep hole segment are relative concepts, that is, the holes of the modified porous carbon carrier are deep hole segments and shallow hole segments from the inside to the outside, and the end of the shallow hole segment away from the deep hole segment is connected to the opening. That is, when the hole is a blind hole, the hole is composed of a deep hole segment-a shallow hole segment from the inside to the outside, and when the hole is a through hole, both ends of the through hole have openings, and the through hole is composed of a shallow hole segment-a deep hole segment-a shallow hole segment.

[0044] Since the wall of the shallow pore section is modified with hydrophilic groups, when the modified porous carbon support and the precursor solution are mixed, the metal ions preferentially coordinate and bind with the hydrophilic groups of the shallow pore section, so that the metal ions are preferentially anchored in the shallow pore section. That is, in the intermediate product obtained at this time, most of the metal ions coordinate with the hydrophilic groups and form in the shallow pore section of the hole, realizing the directional distribution of the metal ions in the shallow pore section of the hole.

[0045] Therefore, after the intermediate products of the directional distribution of metal ions in the shallow hole section of the pore are reduced, most of the nano-metal particles obtained by the reduction of metal ions exist on the wall surface of the shallow hole section, thereby avoiding direct contact between the nano-metal particles and the ionomer. At the same time, it can also avoid the blockage of the deep hole section due to excessive deposition, which affects the mass transfer rate and catalytic effect.

[0046] In summary, the preparation method provided by the present application can realize the directional modification of nano-metal particles at specific positions in the pores of the porous carbon carrier, so as to realize the regulation of the loading position of the metal catalyst, and load the nano-metal particles in the shallow hole section (that is, the superficial position) of the hole. This loading site can not only isolate the direct contact between the nano-metal particles and the ionomer, protect the nano-metal particles from being poisoned by the sulfonic acid groups in the ionomer, but also help to shorten the mass transfer distance, and at the same time avoid the deposition of nano-metal particles in the deep hole section, which causes the pores to be blocked and the mass transfer resistance to increase, thereby ensuring the porous performance of the supported catalyst.

[0047] In some alternative embodiments, the hydrophilic group includes at least one of an oxygen-containing group and a nitrogen-containing group;

[0048] Wherein, the nitrogen-containing group includes at least one of amino, nitro, pyrrole N, pyridinic N, and graphite N;

[0049] The oxygen-containing group includes at least one of a carboxyl group, a carbonyl group, and a hydroxyl group.

[0050] The above hydrophilic groups can coordinate with metal ions, so that the metal ions are preferentially coordinated with the hydrophilic groups and formed in the shallow hole section of the hole, thereby achieving directional distribution of the metal ions in the shallow hole section of the hole.

[0051] In some optional embodiments, the precious metal ions include at least one of platinum ions, palladium ions, rhodium ions, gold ions, and silver ions, and the transition metal ions include at least one of manganese ions, chromium ions, iron ions, cobalt ions, nickel ions, copper ions, and zinc ions.

[0052] Among them, the metal ions are provided by a precursor, and the precursor can be a soluble metal salt. For example, precious metal ions can be provided by precious metal salts containing Pt, Pd, Rh, Au, Ag, etc., and transition metal ions can be provided by transition metal salts containing Mn, Cr, Fe, Co, Ni, Cu, Zn, etc. Among them, the precursor solution can contain only salts that provide a single metal ion, or multiple metal salts can be added at the same time so that the precursor solution contains multiple metal ions.

[0053] The precursor of platinum ions may be chloroplatinic acid in addition to soluble platinum salts such as platinum tetrachloride.

[0054] It should be noted that the mass ratio of the precursor to the modified porous carbon support can be adjusted according to the actual loading amount of the metal particles in the supported catalyst. For example, when the modified porous carbon support and the precursor solution are mixed, the mass ratio of the precursor to the modified porous carbon support is 2:8-6:4 based on the metal elements in the precursor.

[0055] In some optional embodiments, the method for preparing the modified porous carbon support comprises:

[0056] mixing the porous carbon support with a solvent so that the porous carbon support is in a saturated state to obtain a first support;

[0057] Drying at low temperature to make the first carrier lose some water, so that the part of the pores not filled with the solvent is used as a shallow pore section, and the part of the pores filled with the solvent is used as a deep pore section, thereby obtaining a second carrier;

[0058] Performing hydrophilic treatment on the second carrier to form hydrophilic groups on the shallow hole section of the hole and the surface of the second carrier to obtain a third carrier;

[0059] The third carrier is mixed with a solvent to make the third carrier in a saturated state, the hydrophilic groups on the surface of the third carrier are removed, and the third carrier is dried to obtain a modified porous carbon carrier.

[0060] Since the porous carbon carrier has a porous structure, the saturated state in the present application means that the porous carbon carrier absorbs the maximum amount of solvent and reaches the saturated state. At this time, it is considered that the pores (including shallow pore segments and deep pore segments) are filled with solvent.

[0061] One drying causes the first carrier in a saturated state to lose part of the solvent. At this time, the deep part of the pores still adsorbs the solvent and is filled with the solvent (as a deep pore segment), while the part close to the opening (as a shallow pore segment) is not filled with the solvent. At this time, when it is subjected to hydrophilic treatment, since the deep pore segment is filled and protected by the solvent, the hydrophilic group can be avoided from modifying the pore wall of the deep pore segment during the hydrophilic treatment, thereby achieving the formation of hydrophilic groups only on the surface of the shallow pore segment of the pore and the second carrier during the hydrophilic treatment, thereby obtaining a third carrier.

[0062] Furthermore, the third carrier is further mixed with the solvent to make the third carrier in a saturated state. At this time, the shallow pore segment loaded with hydrophilic groups continues to be filled with the solvent and protected. When the hydrophilic groups are removed at this time, the solvent can protect the hydrophilic groups of the shallow pore segment. Therefore, only the hydrophilic groups on the surface of the porous carbon carrier can be removed. Finally, secondary drying is performed to obtain a modified porous carbon carrier in which only the wall surface of the shallow pore segment of the pore is modified with hydrophilic groups, while the wall surface of the deep water segment has no hydrophilic groups.

[0063] Among them, the preparation method of the modified porous carbon carrier is simple to operate and is conducive to mass production. It can realize the directional modification of hydrophilic groups in the shallow pore section of the porous carbon carrier and realize the regulation of the loading position of the precious metal.

[0064] In some optional embodiments, the second carrier has a fluid loss rate of 10%-30% compared to the first carrier.

[0065] It can be understood that the liquid loss rate of the second carrier compared to the first carrier is 10%-30%, which means that: based on the water content of the first carrier in a saturated state being 100%, the liquid loss rate of the first carrier after one drying is 10%-30%, and the water content of the second carrier is 70%-90%.

[0066] The liquid loss rate of the second carrier is too small and the shallow hole section is too shallow, which affects the loading amount of the metal particles, and the metal particles are easily poisoned by the sulfonic acid groups in the ionomer. The liquid loss rate is too large and the shallow hole section is too deep, resulting in too deep deposition of nano-metal particles, still a large mass transfer distance, and blocked pores, resulting in increased mass transfer resistance, leading to low catalytic efficiency. Therefore, the liquid loss rate of the second carrier is controlled to be 10%-30% compared with the first carrier, and the length of the shallow hole section is controlled within a reasonable range, which is beneficial to protecting the nano-metal particles from being poisoned by the sulfonic acid groups in the ionomer and is beneficial to shortening the mass transfer distance.

[0067] Illustratively, the liquid loss rate of the second carrier compared to the first carrier is any value of 10%, 12%, 15%, 17%, 20%, 22%, 25%, 27%, 30%, or between any two values.

[0068] In some optional embodiments, the primary drying temperature is 40°C-80°C.

[0069] The low-temperature drying method is used to slowly evaporate the solvent. On the one hand, it is beneficial to accurately control the liquid loss rate. On the other hand, the low-temperature drying method is beneficial to the uniform distribution of the remaining solvent in the pores of the porous carbon carrier after drying, which is beneficial to the subsequent more uniform distribution of the hydrophilic groups in the shallow pore section of the modified porous carbon carrier, and further beneficial to the uniform distribution of nano-metal particles in the shallow pore section of the modified porous carbon carrier.

[0070] Illustratively, the primary drying temperature is any one of 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, or between any two values.

[0071] In some optional embodiments, the solvent is at least one of water and C1-C4 alcohol.

[0072] The C1-C4 alcohol includes at least one of methanol, ethanol, propanol and butanol.

[0073] The above solvent not only has a good dispersion effect, but is also easy to remove at low temperature, thereby avoiding the introduction of impurities and destroying the structure of the porous carbon carrier.

[0074] In some optional embodiments, the hydrophilic treatment method includes plasma hydrophilic modification treatment, the atmosphere of the plasma hydrophilic modification treatment includes at least one of oxygen, nitrogen, and ammonia, the temperature of the plasma hydrophilic modification treatment is 25°C-40°C, the time of the plasma hydrophilic modification treatment is 10min-60min, and the power of the plasma hydrophilic modification treatment is 50-300W.

[0075] It is understood that when the atmosphere of the plasma hydrophilic modification treatment is oxygen, oxygen-containing groups are introduced, and the oxygen-containing groups include at least one of carboxyl, carbonyl, and hydroxyl groups. When the atmosphere of the plasma hydrophilic modification treatment is nitrogen or ammonia, the modified hydrophilic groups can be in the form of amino, nitro, pyrrole N, pyridine N, graphite N, etc.

[0076] The plasma hydrophilic modification treatment is carried out at the above-mentioned low temperature. Not only does the treatment process not cause damage to the porous carbon carrier, but it also has no effect on the degree of graphitization and the pore structure. The method is simple and conducive to mass production. At the same time, the above-mentioned plasma hydrophilic modification treatment method basically does not introduce impurities, thereby avoiding the introduction of impurities that affect the catalytic performance of the supported catalyst.

[0077] Illustratively, the temperature of the plasma hydrophilic modification treatment is any one of 25°C, 30°C, 35°C, and 40°C.

[0078] Exemplarily, the time of the plasma hydrophilic modification treatment is any value of 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min or between any two values.

[0079] Exemplarily, the power of the plasma hydrophilic modification treatment is any value of 50 W, 100 W, 150 W, 200 W, 250 W, 300 W, or between any two values.

[0080] In some optional embodiments, the step of removing the hydrophilic groups located on the surface of the third carrier includes: performing hydrogen plasma treatment on the surface of the third carrier in a saturated state, the time of the hydrogen plasma treatment is 10min-60min, the temperature of the hydrogen plasma treatment is 25℃-40℃, and the power of the hydrogen plasma treatment is 50W-300W.

[0081] Through hydrogen plasma treatment, the hydrophilic groups on the surface of the third carrier can be effectively reduced and removed. At the same time, the temperature of the hydrogen plasma treatment is low, so that the treatment process does not destroy the graphitization degree and pore structure of the porous carbon carrier. At the same time, the above-mentioned hydrogen plasma treatment method basically does not introduce impurities.

[0082] Exemplarily, the time of hydrogen plasma treatment is any value of 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min or between any two values.

[0083] Illustratively, the temperature of the hydrogen plasma treatment is any one of 25°C, 30°C, 35°C, and 40°C.

[0084] Exemplarily, the power of the hydrogen plasma treatment is any value of 50 W, 100 W, 150 W, 200 W, 250 W, 300 W, or between any two values.

[0085] In some optional embodiments, the reduction process comprises:

[0086] In the liquid phase, the metal ions are reduced to nano-metal particles by the action of a reducing agent; or,

[0087] The intermediate product is heat treated in a reducing atmosphere to reduce the metal ions to nano-metal particles.

[0088] The specific liquid phase reduction or gas phase reduction method can refer to the relevant technology.

[0089] In the liquid phase, the metal ions are reduced to nano-metal particles by the action of a reducing agent, that is, a liquid phase reduction method is adopted, wherein the reducing agent in the liquid phase reduction method includes but is not limited to polyols, sodium borohydride, formaldehyde, formic acid, etc., which can be selected according to actual needs. For example, the reduction is carried out by heating to 120°C-160°C in a polyol, wherein the liquid phase reduction can be assisted by microwave heating for reduction, which is conducive to reducing the metal ions to nano-metal particles.

[0090] Heat treatment of the intermediate product under a reducing atmosphere is also known as gas phase reduction, wherein the gas phase reduction atmosphere includes but is not limited to heat treatment at 200°C-700°C for 0.5h-4h in a reducing atmosphere of hydrogen and / or carbon monoxide, or in a reducing atmosphere of a mixture of hydrogen and an inert gas.

[0091] In the second aspect of this application, please refer to Figure 1 , the present application provides an example of a supported catalyst 100, which is prepared by the preparation method provided in the first aspect of the present application;

[0092] The supported catalyst 100 includes modified porous carbon 11 and nano-metal particles 20 . The nano-metal particles 20 are located on the wall surface of the pore 12 in the shallow hole section.

[0093] It can be understood that the nano metal particles 20 are loaded on the wall surface of the shallow hole segment, that is, the particle size of the nano metal particles 20 is smaller than the pore size of the shallow hole segment, and the shallow hole segment loaded with the nano metal particles 20 still has a pore structure connected to the deep hole segment, ensuring the pore structure of the loaded catalyst 100.

[0094] The present application provides a loaded catalyst 100 prepared by the preparation method provided by the first aspect, wherein the nano-metal particles 20 are loaded on the shallow hole section (i.e., the superficial position) of the hole 12. The loading site can not only isolate the direct contact between the nano-metal particles 20 and the ionomer, protecting the nano-metal particles 20 from the poisoning effect of the sulfonic acid groups in the ionomer, but also helps to shorten the mass transfer distance, while avoiding the deposition of the nano-metal particles 20 in the deep hole section so that the pores are blocked and the mass transfer resistance is increased, thereby ensuring the porous performance of the loaded catalyst 100. In summary, the loaded catalyst 100 can improve the power generation efficiency of the fuel cell after being applied to the fuel cell.

[0095] Optionally, the loading amount of the nano metal particles 20 in the supported catalyst 100 is 20%-60%.

[0096] In a third aspect, the present application provides an example of a fuel cell, which includes the supported catalyst provided in the second aspect of the present application.

[0097] The supported catalyst, preparation method thereof and fuel cell of the present application are further described in detail below in conjunction with the examples.

[0098] Example 1

[0099] A supported catalyst (Pt / C catalyst), the preparation method of which can be found in Figure 2 , which includes:

[0100] S1. Partially immerse the pores with a solvent: Continue to stir and evenly disperse the porous carbon carrier in water to make the porous carbon carrier in a saturated state. At this time, water can completely fill the internal pores of the porous carbon carrier to obtain a first carrier. After filtering the first carrier, dry it in an oven at 60°C to a water loss of 20% to obtain a second carrier.

[0101] S2. The second carrier is subjected to oxygen plasma oxidation treatment to modify the porous carbon surface and the pore walls not filled with water (shallow pore section) with oxygen-containing groups such as carboxyl, carbonyl, and hydroxyl to obtain a third carrier, wherein the temperature of the oxygen plasma oxidation treatment is 25°C, the time of the oxygen plasma oxidation treatment is 30 minutes, and the power of the hydrophilic modification treatment of the oxygen plasma oxidation treatment is 200W.

[0102] S3. Use solvent to completely immerse the holes: fully disperse the third carrier in water again, stir thoroughly to make the third carrier in a saturated state, stop stirring, and filter.

[0103] S4, hydrogen plasma reduction treatment: the surface of the third carrier obtained by filtration in step S3 is subjected to hydrogen plasma treatment to remove oxygen-containing groups on the surface of the third carrier to obtain a fourth carrier; wherein the time of the hydrogen plasma treatment is 30 minutes, the temperature of the hydrogen plasma treatment is 25°C, and the power of the hydrogen plasma treatment is 200W.

[0104] S5. Removing the solvent: drying the fourth carrier to completely remove the water, thereby obtaining a modified porous carbon carrier in which only the pore walls of the shallow pore sections are modified with oxygen-containing groups.

[0105] S6. Pt ion coordination: chloroplatinic acid and the modified porous carbon liquid phase are mixed and dispersed to allow the oxygen-containing groups to adsorb and anchor Pt ions, and filtered to obtain an intermediate product, wherein the mass ratio of chloroplatinic acid to the modified porous carbon is 6:4 based on the platinum element.

[0106] S7. Pt ion reduction: The intermediate product is placed in a CO atmosphere and heat treated at 300°C for 1 h.

[0107] Example 2

[0108] A supported catalyst (Pt / C catalyst), which differs from Example 1 in that:

[0109] S1. Partially immerse the pores with a solvent: Continue to stir and evenly disperse the porous carbon carrier in water to make the porous carbon carrier in a saturated state. At this time, water can completely fill the internal pores of the porous carbon carrier to obtain a first carrier. After filtering the first carrier, dry it in an oven at 60°C to a water loss of 10% to obtain a second carrier.

[0110] Example 3

[0111] A supported catalyst (Pt / C catalyst), which differs from Example 1 in that:

[0112] S1. Partially immerse the pores with a solvent: Continue to stir and evenly disperse the porous carbon carrier in water to make the porous carbon carrier in a saturated state. At this time, water can completely fill the internal pores of the porous carbon carrier to obtain a first carrier. After filtering the first carrier, dry it in an oven at 60°C to a water loss of 30% to obtain a second carrier.

[0113] Comparative Example 1

[0114] A supported catalyst (Pt / C catalyst) differs from Example 1 only in that:

[0115] Chloroplatinic acid is directly mixed and dispersed with the porous carbon carrier liquid phase, and filtered to obtain an intermediate product, wherein the mass ratio of chloroplatinic acid to modified porous carbon is 6:4 based on platinum element.

[0116] The intermediate product was heat treated at 300 °C for 1 h in a CO atmosphere.

[0117] Test example

[0118] The oxygen evolution activity and durability of the catalyst are studied through a series of electrochemical tests (cyclic voltammetry CV, linear sweep voltammetry LSV, etc.). In general, the electrochemical active area ECSA and mass activity MA are used to judge the ORR performance.

[0119] CV test: Place the electrodes in an electrolytic cell to form a three-electrode system. The reference electrode is Hg / Hg2SO4, the counter electrode is a platinum mesh electrode, and the electrolyte is a 0.5M H2SO4 solution saturated with N2 and kept at a constant temperature of 25°C. Open the software, set the scan rate in the CV test window to 50m / s, and scan 20 times (10 cycles) at -0.632 to 0.328V to fully activate the catalyst and stabilize the complex desorption peak. Calculate the electrochemical active area ECSA of the catalyst based on the data of the last cycle.

[0120] Linear sweep voltammetry: In order to evaluate the ORR electrocatalytic performance of the catalyst materials and their performance in the reaction process, cathode polarization measurements were performed and the linear sweep voltammetry (LSV) results were used for judgment. LSV test: The LSV test window was replaced with an O2-saturated 0.1M HC1O4 electrolytic cell (for IR compensation), and the working electrode was kept at a speed of 1600rpm. Scanning was performed at -0.26 to 0.695V at a scan rate of 10mV / s. The kinetic current density was calculated from the measured current density and the limiting current density, and the mass specific activity MA was calculated from the kinetic current density and the actual mass of the precious metal.

[0121] The oxygen content of the modified porous carbon support obtained in step S5 of Examples 1-3 and the porous carbon support used in Comparative Example 1 is expressed as modified porous carbon / porous carbon oxygen content in Table 1. The electrochemical properties of the supported catalyst (Pt / C catalyst) of each Example and Comparative Example are shown in Table 1.

[0122] Table 1 Test results

[0123]

[0124] Among them, according to the oxygen content of the modified porous carbon / porous carbon, it can be seen that the oxygen content of Examples 1-3 is increased after the modification treatment compared with the unmodified comparative example 1. That is, combined with the modification method, it can be inferred that hydrophilic oxygen-containing groups are formed in the modified porous carbon, and the content is positively correlated with the water loss after filtering the first carrier and drying it in an oven at 60°C.

[0125] According to Examples 1-3 and Comparative Example 1, under the same loading conditions, the electrochemical active area ECSA changes very little, while the mass specific activity changes greatly, indicating that the difference in the particle size of the Pt particles in the Pt / C catalysts in Examples 1-3 and Comparative Example 1 is very small. The reason for the large change in their mass specific activity lies in the distribution position of the Pt particles.

[0126] This means that loading the nano-metal particles in the shallow hole section (i.e., the superficial position) of the pores is beneficial to improving the catalytic performance of the supported catalyst.

[0127] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a supported catalyst, characterized in that: The following steps are involved: mixing the modified porous carbon support and the precursor solution to obtain an intermediate product; The modified porous carbon carrier has holes, the holes have openings that penetrate the surface of the modified porous carbon carrier, the holes have shallow hole sections close to the openings and deep hole sections away from the openings, the holes are located on the walls of the shallow hole sections and are modified with hydrophilic groups, the precursor solution contains metal ions for coordination with the hydrophilic groups, and the metal ions include at least one of noble metal ions and transition metal ions; The intermediate product is subjected to reduction treatment to reduce the metal ions into nano-metal particles.

2. The preparation method according to claim 1, characterized in that: The hydrophilic group includes at least one of an oxygen-containing group and a nitrogen-containing group; Wherein, the nitrogen-containing group includes at least one of amino, nitro, pyrrole N, pyridinic N, and graphite N; The oxygen-containing group includes at least one of a carboxyl group, a carbonyl group, and a hydroxyl group; Optionally, the precious metal ions include at least one of platinum ions, palladium ions, rhodium ions, gold ions, and silver ions, and the transition metal ions include at least one of manganese ions, chromium ions, iron ions, cobalt ions, nickel ions, copper ions, and zinc ions.

3. The preparation method according to claim 1 or 2, characterized in that: The preparation method of the modified porous carbon carrier comprises: Mixing a porous carbon support with a solvent so that the porous carbon support is in a saturated state to obtain a first support; Drying once so that the first carrier loses part of the solvent, so that the part of the pores not filled with the solvent serves as a shallow pore section, and the part of the pores filled with the solvent serves as a deep pore section, thereby obtaining a second carrier; Performing a hydrophilic treatment on the second carrier to form the hydrophilic groups on the shallow hole section of the hole and the surface of the second carrier to obtain a third carrier; The third carrier is mixed with a solvent to make the third carrier in a saturated state, the hydrophilic groups on the surface of the third carrier are removed, and secondary drying is performed to obtain the modified porous carbon carrier.

4. The preparation method according to claim 3, characterized in that: The second carrier has a liquid loss rate of 10%-30% compared to the first carrier; Optionally, the solvent is at least one of water and C1-C4 alcohol.

5. The preparation method according to claim 3, characterized in that: The primary drying temperature is 40°C-80°C.

6. The preparation method according to claim 3, characterized in that: The hydrophilic treatment method includes plasma hydrophilic modification treatment, the atmosphere of the plasma hydrophilic modification treatment includes at least one of oxygen, nitrogen, and ammonia, the temperature of the plasma hydrophilic modification treatment is 25°C-40°C, the time of the plasma hydrophilic modification treatment is 10min-60min, and the power of the plasma hydrophilic modification treatment is 50W-300W.

7. The preparation method according to claim 3, characterized in that: The step of removing the hydrophilic groups on the surface of the third carrier includes: performing hydrogen plasma treatment on the surface of the third carrier in a saturated state, the time of the hydrogen plasma treatment is 10min-60min, the temperature of the hydrogen plasma treatment is 25℃-40℃, and the power of the hydrogen plasma treatment is 50-300W.

8. The preparation method according to claim 1 or 2, characterized in that: The reduction process comprises: The metal ions are reduced to nano-metal particles by a reducing agent in a liquid phase; or, The intermediate product is heat treated in a reducing atmosphere to reduce the metal ions to nano metal particles.

9. A supported catalyst, characterized in that It is prepared by the preparation method according to any one of claims 1 to 8; Wherein, the supported catalyst comprises the modified porous carbon and the nano metal particles, and the nano metal particles are located on the wall surface of the hole located in the shallow hole section.

10. A fuel cell, characterized in that: The method comprises the supported catalyst according to claim 9.

Citation Information

Patent Citations

  • Carbon carrier for fuel cell and preparation and application of platinum-based catalyst of carbon carrier

    CN116598515A

  • Surface modified porous carbon carrier as well as preparation method and application thereof

    CN118448660A

  • Carbon nanofiber with skin-core structure, method of producing the same, and products comprising the same

    US20100167177A1